Alterações nas funções executivas, impulsividade e agressividade em indivíduos dependentes de crack - Teixeira, Vanina Papini Góes (2014)
Even though crack use is nowadays a major public health problem, there is a few scientific data about executive functioning déficits and interferences on impulsive and aggressive behavior of the exposure to the psychoactive substance. The aim of this research was to evaluate the existence of deficits in executive functions in crack users and in ex-users, in abstinence for sixty daysat least, after a minimum period of sixty days of abstinence compared to healthy controls. We also tried to find out to identify the levels of impulsivity and aggression in individuals who used crack. It was conducted a quantitative quasi-experimental study. Thus, a sociodemographic questionnaire was applied that allowed the identification of the subject and the crack’s standard use, after that the neuropsychological assessment was administered, which enables the identification of performancein scales investigating executive function, then the levels impulsiveness and aggression assessment. Was used standardized instruments, including the BETA-III (estimated IQ), BAI (anxiety assessment), the BDI (for depression assessment), the BROWN’s scale (assessment of attention deficit), the BIS-11 (evaluation of impulsivity), the questionnaire BUSS-PERRY (assessment of aggressiveness), the Stroop Test (evaluation of attention, inhibitory control, and flexibility), the WCST (evaluation of flexibility) and IGT (evaluation of decision making). The instruments were administered to 102 subjects divided into three distinct groups with harmonic distribution, the G1 group was formed by 34 crack users, the G2 group by 34 abstinents crack users and the G3 group, formed by 34 controls. The subjects were matched for age, years of education, socioeconomic status and IQ. The subjects of G1 group, the crack’s users, performed worse than ex-users (p <0.05) and than controls (p <0.05) in the executive functioning assessment and higher levels of impulsivity and aggression; subjects from group G2 performed worse than subjects in the control group, G3, but better than the crack user group, G1. The results indicate that crack use is associated with deficits in executive functions, and has interference in high levels of impulsivity and aggression, problems associated with prefrontal brain regions. Identification of neuropsychological impairments, as well as the impulsive and aggressive behavior in individuals with experience with the crack may be useful for developing more effective treatment programs, thus reducing the high levels of non-adherence to treatment and high relapses rates.